1990
DOI: 10.1017/s0022029900026820
|View full text |Cite
|
Sign up to set email alerts
|

Effects of added salts on the heat stability of recombined concentrated milk

Abstract: SummaryChanges in heat stability and Ca2+ activity of recombined concentrated milk (18% solids non-fat:8% fat) induced by the additions of 0·011–0·217 mol phosphate/kg skim milk solids (SMS), 0·022–0·217 mol citrate/kg SMS, 0·011–0·022 mol Ca/kg SMS and 0·016–0·067 mol EDTA/kg SMS were evaluated. Heat stability was assessed using an objective method which involved determination of viscosity after heating under controlled conditions. Low levels of added phosphate and citrate generally effected an acid shift of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 24 publications
4
40
0
Order By: Relevance
“…This is in agreement with earlier reports that showed that a seasonal increase in the ratio of calcium to orthophosphate could be correlated with a reduction in heat stability [30]. Lowering free calcium ion activity through the addition of calcium sequestering agents has also been shown to improve the heat stability of preheated milk powders [6]. In our experiments we have seen that additional factors linked to the stability of the micelles and the aggregation states of the proteins may also be involved.…”
Section: Soluble Aggregate Compositionsupporting
confidence: 93%
See 2 more Smart Citations
“…This is in agreement with earlier reports that showed that a seasonal increase in the ratio of calcium to orthophosphate could be correlated with a reduction in heat stability [30]. Lowering free calcium ion activity through the addition of calcium sequestering agents has also been shown to improve the heat stability of preheated milk powders [6]. In our experiments we have seen that additional factors linked to the stability of the micelles and the aggregation states of the proteins may also be involved.…”
Section: Soluble Aggregate Compositionsupporting
confidence: 93%
“…In this case, it appears that reducing the mineral content through lactose standardization has reduced the degree of aggregation. This has parallels with earlier work [6] where heat stability could be improved by reducing calcium ion activity. Figure 2 shows the profiles for the milk powders produced in trial 1.…”
Section: Change In the Size Distributionssupporting
confidence: 75%
See 1 more Smart Citation
“…Calcium and phosphorus migrate from the micelle and calcium phosphate becomes more soluble. This results in increase of free ionic calcium, causing liberation of hydrogen ions and decrease in pH (Augustin & Clarke, 1990). The distribution of caseins and calcium between the serum and micellar phase is pH and temperature dependent.…”
Section: The Effect Of Ph Reduction On Gelation Of Uht Milk At 25 °Cmentioning
confidence: 99%
“…Generally the addition of calcium salts to milk causes an increase in serum calcium ions, an increase in calcium in the colloidal phase, a decrease in pH, and a decrease in heat stability. Reduction of the calcium ion concentration by the addition of phosphate or citrate generally causes an increase in heat stability [1,23].…”
Section: Introductionmentioning
confidence: 99%